Development of My Decision/Mi Decisión, a web-based decision aid to support permanent contraception decision making - Elizabeth A. Mosley; Nikki Zite; Christine Dehlendorf; Ashley Deal; Raelynn O'Leary; Sharon Achilles; Amber E. Barnato; Daniel Hall; Sonya Borrero (Elsevier, 2023)
Objective: To develop a patient-centered, web-based decision aid to support informed and value-concordant decision making among Medicaid enrollees considering tubal sterilization. Methods: We used the Ottawa Decision Support Framework and the International Patient Decision Aids Standards (IPDAS) to guide systematic development of our decision aid. We interviewed 15 obstetrician-gynecologists and 40 women, who had considered or were considering tubal sterilization. A Steering Committee-comprising healthcare providers, social scientists, reproductive health and justice advocates, and people with lived experience-provided feedback and direction. We developed English and Spanish prototypes, which were beta tested with 24 women. Results: The resulting web-based My Decision/Mi Decisión tool (English/Spanish) includes written and video information about tubal sterilization procedures; an interactive table of contraception options; values clarification exercises; reflection and deliberation; knowledge checks; and a summary report to share with one's provider. Users found the decision aid to be informative, engaging, easy to use, and helpful in informing contraception decision making. Conclusion: My Decision/Mi Decisión is a scalable tool that could be implemented widely to support informed decision making about tubal sterilization. Innovation: This is a novel and timely web-based decision tool for tubal sterilization, when demand for permanent contraception is rapidly increasing post-Dobbs. While designed for Medicaid enrollees, further investigation will explore more generalized use.